THE ROLE OF UNBALANECED DIET IN METABOLIC SYNDROME PROGRESSION - Karmazina, Iryna; Isaieva, Inna; Kovalyov, Maksim; Pavlov, Oleksii (Sworld-Us Conference proceedings, 2024)
This review is devoted to analysis of recent data concerning the role of unbalanced diet in metabolic syndrome progression. The impact of unbalanced diet on lipids and carbohydrates metabolism is demonstrated. The mechanisms of obesity and insulin resista